Extracellular vesicles derived from Lactobacillus gasseri GFC-1220 alleviate inflammation via the TLR4/NF-κB signaling pathway in LPS-stimulated RAW264.7 macrophages - Jin-Ah Koh; Minh Ha Le; Hyo-Jun Lee; Jin-Woo Min; Mi Jung Kim; Hee-Cheol Kang; Yeon-Ju Kim (Scientific Reports)
Abstract Studies on the impact of gram-positive extracellular vesicles have paved the way for novel medical advancements. These vesicles serve as efficient carriers of microbial molecules to target cells, thereby influencing human pathophysiological processes. Thus, this study aimed to investigate the anti-inflammatory properties of extracellular vesicles derived from Lactobacillus gasseri GFC-1220 (LEVs) in lipopolysaccharide (LPS)-stimulated RAW264.7 macrophages. LEVs were characterized using transmission electron microscopy, nanoparticle tracking analysis, and dynamic light scattering measurements to examine their morphology, size, and concentration. We further assessed the anti-inflammatory effects of LEVs and their underlying mechanism in LPS-stimulated RAW264.7 macrophages. Our findings revealed that LEVs did not cause cytotoxic effects and significantly decreased the level of mitochondria superoxide and reactive oxygen species production. In addition, these vesicles effectively inhibited the LPS-induced activation of TLR4/NF-κB signaling pathway, consequently suppressing the secretion and expression of various pro-inflammatory mediators and cytokines. These included a reduction in the production of NO and PGE2, along with their corresponding producer enzymes iNOS and COX-2, as well as IL-6, TNF-α, and IL-1β cytokines. These findings strongly suggest that LEVs have significant potential for the development of new anti-inflammatory agents.